2022
DOI: 10.1111/inm.13104
|View full text |Cite
|
Sign up to set email alerts
|

The physical health nurse consultant and mental health consumer: An important therapeutic partnership

Abstract: People diagnosed with mental illness (hereon referred to as consumers) experience a disproportionately lower life expectancy of up 30 years compared to the general population. Systemic issues such as diagnostic overshadowing and stigma from healthcare professionals have inhibited the development of positive therapeutic partnerships that enable consumers to seek and engage support for their physical health concerns. Consumers have called for healthcare professionals to skillfully develop and prioritize therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Recent Australian studies involving patient participants found they prioritise their physical health, but experience barriers and desire support with this (21,22). The evidence is mixed regarding GP attendance by patients with SMI.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Recent Australian studies involving patient participants found they prioritise their physical health, but experience barriers and desire support with this (21,22). The evidence is mixed regarding GP attendance by patients with SMI.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%